Carina™ modular robotic-assisted left lower lobectomy after neoadjuvant chemoimmunotherapy for stage IIIA squamous cell lung cancer: a case report - Chen, Hao; Yin, Hancheng; Zheng, Bin; Xu, Chi; Chen, Chun; Xu, Guobing (AME Case Reports, 2026)
Background: Neoadjuvant chemoimmunotherapy has become a standard approach for locally advanced non-small cell lung cancer (NSCLC), enhancing resectability. However, it also increases surgical complexity because of treatment-induced fibrosis—a challenge well addressed by robotic-assisted thoracic surgery (RATS). This report demonstrates the successful application of a modular robotic platform for post-neoadjuvant left lower lobectomy in a patient with stage IIIA squamous NSCLC, highlighting its precision and feasibility in complex oncologic resections.Case Description: A 51-year-old man was diagnosed with squamous cell carcinoma of the left lower lobe (cT2aN2M0) and achieved a partial response following pembrolizumab plus chemotherapy. After completing neoadjuvant chemoimmunotherapy, robot-assisted left lower lobectomy with systematic lymph node dissection was performed using the Carina™ Modular Robotic System (Ronovo Surgical, Shanghai, China) because of anticipated pleural adhesions and the complex anatomical location of enlarged lymph nodes. The robotic platform demonstrated excellent outcomes: 20 mL blood loss, 5-minute docking time, and 141-minute console time. Intraoperatively, severe pleural adhesions were encountered but successfully managed with robotic assistance, enabling complete dissection and safe tumor resection. The patient recovered rapidly, with chest tube removal by postoperative day 5 and discharge on day 7. Pathology revealed a major pathological response (MPR) with negative bronchial margins.Conclusions: This case demonstrates the technical feasibility of the Carina™ system for complex post-neoadjuvant lobectomy in a patient with stage IIIA squamous NSCLC. Acceptable short-term perioperative outcomes were observed despite pleural adhesions and nodal complexity. Further experience and larger studies are needed to evaluate the potential role of this platform in thoracic surgery.